Association between espresso coffee and serum total cholesterol: the Tromsø Study 2015–2016. Issue 1 (10th May 2022) - Svatun, Åsne Lirhus; Løchen, Maja-Lisa; Thelle, Dag Steinar; Wilsgaard, Tom
Abstract : Background: Coffee raises serum cholesterol because of its diterpenes, cafestol and kahweol, and the effect varies by brewing method. Population-based research on espresso coffee's impact on serum cholesterol is scarce. Our aim was to examine how various brewing methods, in particular espresso, were associated with serum total cholesterol (S-TC). Methods: We used cross-sectional population data from the seventh survey of the Tromsø Study in Northern Norway (N=21 083, age ≥40 years). Multivariable linear regression was used to assess the association between S-TC as the dependent variable and each level of coffee consumption using 0 cups as the reference level, adjusting for relevant covariates and testing for sex differences. Results: Consumption of 3–5 cups of espresso daily was significantly associated with increased S-TC (0.09 mmol/L, 95% CI 0.01 to 0.17 for women and 0.16 mmol/L, 95% CI 0.07 to 0.24 for men), compared with participants drinking 0 cups of espresso per day. Consumption of ≥6 cups of boiled/plunger coffee daily was also associated with increased S-TC (0.30 mmol/L, 95% CI 0.13 to 0.48 for women and 0.23 mmol/L, 95% CI 0.08 to 0.38 for men), compared with participants drinking 0 cups of boiled/plunger coffee. Consumption of ≥6 cups of filtered coffee daily was associated with 0.11 mmol/L (95% CI 0.03 to 0.19) higher S-TC levels for women but not for men. Instant coffee consumption had a significant linear trend but showed no dose–response relationship when excluding participants not drinking instant coffee. There were significant sex differences for all coffee types except boiled/plunger coffee. Conclusion: Espresso coffee consumption was associated with increased S-TC with significantly stronger association for men compared with women. Boiled/plunger coffee was associated with increased S-TC in both sexes and with similar magnitude as shown in previous research. Filtered coffee was associated with a small increase in S-TC in women. Further research on espresso and S-TC is warranted.